Supporting Newly Qualified Diagnostic Radiographers: Are We Getting It Right? - Harvey-Lloyd, Jane; Jane Morris (International Journal of Practice-based Learning in Health and Social Care, 2020)
The NHS is facing a rising demand in services and consequently, newly qualified practitioners are required to possess a much wider set of skills than ever before. In diagnostic radiography, this pressure is underpinned by the expanding role that diagnostic imaging now plays in many patient pathways. Despite the need for structured support for graduates which has been acknowledged by a range of studies and the introduction of the Preceptorship Framework for Newly Registered Nurses, Midwives and Allied Health Professionals (Department of Health, (DoH), 2010) the uptake in radiography is limited. A longitudinal study employed an interpretive phenomenological methodology collating data from nine participants during their first year as band five radiographers. Each participant was interviewed at three, six and twelve months. Six main themes were identified during a wider PhD study Being and Becoming a Diagnostic Radiographer (Harvey-Lloyd, 2018). This article explores one of the key sub themes ‘structured support’ which strongly featured in the three- and six-month interviews. Two of the nine participants received a structured support programme during their first 12 months of transition as newly qualified radiographers. These programmes focussed on the completion of tasks and were mechanistic in approach. This type of support ignores the process of transformation into the role of a diagnostic radiographer and fails to adequately support those from Generation Z. A model of preceptorship is proposed which combines skills and competence development, supporting transition and personal and professional development; thus, providing the newly qualified radiographers with a holistic range of support.